Evaluation of leed "innovation in design process" and "location and linkages" case study: Diyarbakir Turkey. - Tuna Taygun, G.; Darçın, Polat; Müjdem Vural, Sadiye (Open House International Association P.O. Box 74, Gateshead, Tyne and Wear, 2015)
The paper focuses on the LEED rating system of Diyarbakir Houses to an assessment with respect to "Innovation in Design Process and Location & Linkages", assuming to conduct a trial of the building assessment and certification systems, which were highly popular in Europe and in the U.S. in the 1990s and in Turkey in the 2000s, on the "traditional building". The aim of the paper is to bring a criticism of and suggestions to the LEED credits in connection with environmentalist design criteria, and to be able to determine that these credits, which are limited in the first place, may already be part of the design of traditional buildings in Turkey. Three different typological houses of Diyarbakir were selected for the research and detail evaluated with the scope of LEED for Homes credits. Using this assessment system, old Diyarbakir houses known to involve many successful solutions in terms of factors related to the environment and the user were assessed. The assessment revealed the fact that these houses, which are in harmony with the environment, are energy-efficient, use water and resources optimally, are successful in waste management, meet their users' biological, psychological and social needs and do not cause health problems for their users' and the environment scored low in LEED.
Keywords: Certification systems; Diyarbakir houses; LEED; Traditional buildings